2018
DOI: 10.4314/ajoh.v8i1.178494
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of infective endocarditis among dental students and interns in seven Nigerian Universities

Abstract: Objective: Infective Endocarditis is a potentially life-threatening infection that could occur after an invasive dental procedure. associated with bacteria and high risk cardiac abnormalities. It is usually The depth of knowledge of infective endocarditic amongst dental students in developing countries is rarely reported and information relating to this is sparse in Nigeria. This study therefore aimed to determine the knowledge of IE amongst dental students and interns of Nigeria Universities. METHODS: This cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…17 In Nigeria, it was reported that participants' sources of information about infective endocarditis were lectures (54.5%), internet (34.6%), and textbooks (2.2%). 18 Amoxicillin was the most commonly prescribed antibiotics by dentists in our study for prophylaxis against infective endocarditis (90.7%), followed by Augmentin (37.4%), while the timing of administering prophylactic antibiotics was stated to be 30-60 minutes before the procedure by the majority of participant dentists (86.8%). Other study noted that antibiotic prophylaxis is recommended for invasive dental processes that comprise the operation of gingival tissue or periapical section or perforation of the mucosa when implemented on high-risk persons.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…17 In Nigeria, it was reported that participants' sources of information about infective endocarditis were lectures (54.5%), internet (34.6%), and textbooks (2.2%). 18 Amoxicillin was the most commonly prescribed antibiotics by dentists in our study for prophylaxis against infective endocarditis (90.7%), followed by Augmentin (37.4%), while the timing of administering prophylactic antibiotics was stated to be 30-60 minutes before the procedure by the majority of participant dentists (86.8%). Other study noted that antibiotic prophylaxis is recommended for invasive dental processes that comprise the operation of gingival tissue or periapical section or perforation of the mucosa when implemented on high-risk persons.…”
Section: Discussionmentioning
confidence: 75%
“…17 Moreover, in Nigeria, they reported differences in dentists' knowledge on infective endocarditis according to their age (p=0.035), educational level (p=0.023), but not according to their gender. 18…”
Section: Discussionmentioning
confidence: 99%